Pengaruh Kemampuan, Motivasi Dan Locus Of Control Terhadap Kinerja Individu Melalui Pemediasian Self Efficacy - Jaya, Denny Kumala; Maryati, Tri (Universitas Muhammadiyah Yogyakarta, 2010)
This research aim to test performance which influenced by ability, Motivation, and Locus of Control with Variabel Self Efficacy as mediasi. Population in this research is employees Edukatif in University of Ahmad Dahlan (UAD) with number of samples or data amount which processed is 103 kuisioner. In this research data analyzer applies SEM ( Structural Equation Modeling) with help of program Sofware AMOS 60 for windows. This research proves that ability of influential positive and not significant to self efficacy, motivation influential positive and significant to self efficacy, locus of control influential positive and not significant to self efficacy and self efficacy influential positive and significant to performance, ability of influential positive indirect and not significantÂ to performance as mediasi by self efficacy, motivation influential positive indirect and significant to performance as mediasi by self efficacy, locus of control influential positive indirect and significant to performance in mediasi by self efficacy. Analysis from result, show that model goodness of fit tested at research of approximant overall of can fulfill criterion level fit. Which the result have been solvent of confirmation the factor from a concept through empirical indicatorss and able to measure influence between factors based on the existing theory.